Laser Induced Fluorescence of 1,3 Benzodioxole in a Supersonic Jet - Hassan, Karim H.; Jawad, Hussein A. (Iraqi Journal of Laser, 2004)
Fluorescence excitation by Nd:YAG pumped dye laser and single vibrational level fluorescence spectra of 1,3 benzodioxole in a supersonic jet have been obtained and interpreted. The previous assignment of the 0 0 0 band was incorrect. In addition, many other bands involving n20 and n19 vibrations of a2 symmetry were confirmed. As far as a1 totally symmetric vibration is concerned. The n14 was assigned to be located in the fivemembered ring whereas n13 seem to be located in the benzene ring as a result of the electronic transition in the benzene ring which affects n13 and not n14 wavenumber.